A neglected pool of labour? Frontline service work and hotel recruitment in Glasgow. Issue 3 (26th March 2018) - Bolton, Sharon C.; Laaser, Knut; McGuire, Darren; Duncan, Ashley
Abstract : The paper presented considers soft skills in the hospitality sector and explores how managers in four hotels in Glasgow, Scotland enact recruitment and selection processes. Empirically, the analysis is based on a rich cross case comparison including interviews, observations, attendance at training events and analysis of hotels' recruitment and selection policies. Conceptually, the analysis draws on the work of Pierre Bourdieu and Andrew Sayer, portraying an understanding of social class as a social, economic, and cultural category and people's agency as shaped by their habitus and lay normativity. Crucially, the paper reveals the pivotal role individual managers play in enabling and constraining opportunities for employment in the enactment of hotel recruitment policy and engagement with job applicants and new recruits. Overall, the analysis suggests that, despite many deterministic analyses of class, an organization's recruitment, learning and development strategies, plus management's commitment to make a difference, can positively impact on those who might otherwise be part of a neglected pool of labour.